Motherwork Under the State: The Maternal Labor of Formerly Incarcerated Black Women. (13th February 2018) - Gurusami, Susila
Abstract: Although Black mothers are disproportionately represented among formerly incarcerated mothers in the United States, existing research has largely neglected to document the challenges they face in resuming their parenting roles after prison or jail. This study addresses this gap using 18 months of participant observations with formerly incarcerated Black women to examine how state surveillance under post-release supervision and child welfare services shapes and constrains formerly incarcerated Black women's mothering practices. The study develops a typology of three context-specific strategies these women employ to anticipate, react to, and cope with state interventions that threaten their mothering: collective motherwork, hypervigilant motherwork, and crisis motherwork. These findings suggest that contrary to popular constructions of formerly incarcerated Black women as negligent mothers, they navigate multiple, overlapping sources of violence to protect their children. Yet, the labor of navigating the state structures that put their children at risk often placed these women in conflict with the state. This paradox suggests the state criminalizes the maternal labor of formerly incarcerated Black women and that these state logics are used to justify state intervention in Black women's post-incarceration parenting.